2015
DOI: 10.1038/ncomms8675
|View full text |Cite
|
Sign up to set email alerts
|

A novel UCS memory retrieval-extinction procedure to inhibit relapse to drug seeking

Abstract: We recently reported that a conditioned stimulus (CS) memory retrieval-extinction procedure decreases reinstatement of cocaine and heroin seeking in rats and heroin craving in humans. Here we show that non-contingent cocaine or methylphenidate injections (UCS retrieval) 1 h before the extinction sessions decreases cocaine-priming-induced reinstatement, spontaneous recovery, and renewal of cocaine seeking in rats. Unlike the CS-based memory retrieval-extinction procedure, the UCS memory retrieval manipulation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(142 citation statements)
references
References 72 publications
7
135
0
Order By: Relevance
“…Recently, it has been demonstrated in several addictionrelated procedures that conducting extinction training following a brief memory retrieval session prevents relapse to drugs seeking (Luo et al, 2015;Ma et al, 2012;Millan et al, 2013;Sartor and Aston-Jones, 2014;Xue et al, 2012). Based on previous similar studies in fear conditioning procedures (eg, Liu et al, 2014;Monfils et al, 2009), it has been postulated that extinction training performed within the 'reconsolidation window' leads to incorporation of the new information (cue-nothing association) into the original cuereinforcement memory trace (eg, cue-drug) (Millan et al, 2013;Monfils et al, 2009;Sartor and Aston-Jones, 2014;Xue et al, 2012), rather than creating a competing memory as in regular extinction (Bouton, 2002;Milton and Everitt, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated in several addictionrelated procedures that conducting extinction training following a brief memory retrieval session prevents relapse to drugs seeking (Luo et al, 2015;Ma et al, 2012;Millan et al, 2013;Sartor and Aston-Jones, 2014;Xue et al, 2012). Based on previous similar studies in fear conditioning procedures (eg, Liu et al, 2014;Monfils et al, 2009), it has been postulated that extinction training performed within the 'reconsolidation window' leads to incorporation of the new information (cue-nothing association) into the original cuereinforcement memory trace (eg, cue-drug) (Millan et al, 2013;Monfils et al, 2009;Sartor and Aston-Jones, 2014;Xue et al, 2012), rather than creating a competing memory as in regular extinction (Bouton, 2002;Milton and Everitt, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous similar studies in fear conditioning procedures (eg, Liu et al, 2014;Monfils et al, 2009), it has been postulated that extinction training performed within the 'reconsolidation window' leads to incorporation of the new information (cue-nothing association) into the original cuereinforcement memory trace (eg, cue-drug) (Millan et al, 2013;Monfils et al, 2009;Sartor and Aston-Jones, 2014;Xue et al, 2012), rather than creating a competing memory as in regular extinction (Bouton, 2002;Milton and Everitt, 2012). However, several studies on fear memories showed that postretrieval extinction did not always prevent reinstatement of fear behavior (Chan et al, 2010;Costanzi et al, 2011;Ishii et al, 2015;Soeter and Kindt, 2011), and studies on drug relapse showed attenuation, but not always prevention of relapse to drug seeking (Luo et al, 2015;Xue et al, 2012). Comparative studies have indicated that counterconditioning may have a stronger suppressive effect on relapse of memories, compared with extinction (Tunstall et al, 2012;Van Gucht et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We recently hypothesized (22,23) that a potential reason for the limited translational utility of the classical CS-induced retrieval and reconsolidation interference procedure is that the neuropharmacological manipulations interfere only with reconsolidation of memories selectively associated with the reactivated CS without affecting memories associated with other CSs or the UCS (the drug) itself. In the case of nicotine addiction, smoking is associated with multiple CSs that vary across individuals (24).…”
mentioning
confidence: 99%
“…Based on these considerations and results from threat (fear) conditioning studies showing that interference with memory reconsolidation after memory retrieval by the UCS (aversive shock) prevents subsequent threat conditioning induced by multiple CSs (2527), we recently developed a UCS-induced memory retrieval–reconsolidation interference procedure and demonstrated its efficacy in decreasing cocaine relapse and craving in rat models (22). However, a limitation of the procedure we introduced in Luo et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation